Analysis of the effect of a series of back twist blade configurations for an active pitch-to-stall floating offshore wind turbine - Ward, Dawn; Collu, Maurizio; Sumner, Joy (Journal of Offshore Mechanics and Arctic Engineering, 2020)
For a turbine mounted on a floating platform, extreme induced loads can be increased by up to 1.6 times those experienced by a turbine situated on a fixed base. If these loads cannot be reduced, towers must be strengthened which will result in increased costs and weight. These tower loads would be additionally exasperated for a pitch-to-feather controlled turbine by a phenomenon generally referred to as “negative damping,” if it were not avoided. Preventing negative damping from occurring on a pitch-to-feather controlled floating platform negatively affects rotor speed control and regulated power performance. However, minimizing the blade bending moment response can result in a reduction in the tower fore-aft moment response, which can increase the tower life. A variable-speed, variable pitch-to-stall (VSVP-S) floating semi-submersible wind turbine, which does not suffer from the negative damping and hence provides a more regulated power output, is presented. This incorporates a back twist blade profile such that the blade twist, starting at the root, initially twists toward stall and, at some pre-determined “initiation” point, changes direction to twist back toward feather until the tip. Wind frequency weighting was applied to the tower axial fatigue life trends of different blade profiles and a preferred blade back twist profile was identified. This had a back twist angle of −3 deg and started at 87.5% along the blade length and achieved a 5.1% increase in the tower fatigue life.